Assessing the relationships between self‐reports of childhood adverse experiences and DSM‐5 alternative model of personality disorder traits and domains: A study on Italian community‐dwelling adults. (24th June 2019) - Borroni, Serena; Somma, Antonella; Krueger, Robert F.; Markon, Kristian E.; Perego, Gaia; Pietrobon, Andrea; Turano, Elisa; Fossati, Andrea
Abstract: A body of research suggests that child maltreatment may not represent an uncommon phenomenon. Adverse childhood experiences have been consistently linked to a variety of mental disorders, including personality disorder. Starting from these considerations, we aimed at testing the associations between retrospective self‐reports of childhood abuse and Personality Inventory for DSM‐5 (PID‐5) traits and domains in a sample of community‐dwelling adult participants ( N = 369; 41.2% male). PID‐5 scales yielded 63 (52.5%) rank‐order correlations with self‐reports of childhood abuse that were significant at Bonferroni‐corrected p level (i.e. p < 0.00042), with values ranging from 0.18 to 0.36. According to Fisher's z ‐test for correlation coefficient homogeneity, the wide majority of the correlations were reproduced across male participants and female participants. Partial rank‐order correlation analyses highlighted specific personality profiles that were uniquely, albeit modestly associated with memories of childhood abuse. Confirming and extending previous findings, our results showed that retrospective reports of childhood abuse are significantly, albeit moderately associated with different dysfunctional personality traits, at least in Italian community‐dwelling adults. As a whole, our data seemed to stress the importance of PID‐5 traits and domains in improving our understanding of the relationships between self‐reports of childhood abuse and dysfunctional personality dimensions in adulthood. © 2019 John Wiley & Sons, Ltd.